INFLUENCE OF A BLEND OF DIETARY ESSENTIAL AMINO ACIDS ON GROWTH, ENZYMATIC ACTIVITY, AND INTESTINAL HISTOLOGY OF BLUE DISCUS - Rudã Fernandes Brandão SANTOS; Mayara Schueroff SIQUEIRA; Ryuller Gama Abreu REIS; Weliton Vilhalba SILVA; Henrique Momo ZIEMNICZAK; Claucia Aparecida HONORATO (Boletim do Instituto de Pesca)
Symphysodon aequifasciatus is a fish with a disk-shaped body and bright colors, important characteristics of ornamental fish. We evaluated amino acid supplementation strategies to reduce crude protein in the diet for evaluation of performance, the content of digestive enzymes, liver metabolism, and intestinal histopathology. A total of 180 fish were randomly distributed in 12 separate 50 L glass aquariums, consisting of a completely randomized design with four treatments (DC - Control diet with 34.4% crude protein; DL - Control diet plus 1% of lysine; DEAA - Control diet plus 1% free essential amino acids (threonine, phenylalanine, leucine, valine, arginine, and tryptophan); and DHP - Diet with a high level of crude protein 48.4%), three repetitions, lasting 60 days. The use of DL and DEAA diets resulted in higher intestinal villus height and higher zootechnical performance. The use of DL diet increased alkaline phosphatase and digestive amylase activity. The use of DHP diets promotes severe liver changes due to increased activity of Alanine aminotraserase. Therefore, it was possible to observe that the use of amino acids can supply the nutritional need of blue discus. Supplementation of diets with AAs allows the reduction of dietary protein, which is a strategy for feeding management.